Pop-Up Book Media Assisted By QR Code For Second-Grade Elementary School Students - Widarini, Ni Kadek Lia; Margunayasa, I Gede; Rati, Ni Wayan (Journal for Lesson and Learning Studies, 2022)
The teacher only uses books in learning activities even though the book has many shortcomings, such as an unattractive presentation. Students also need help understanding each material; more material is presented in the explanation book. This research aims to develop a pop-up book media with the help of a QR Code on the theme of 8 sub-themes 1 for second-grade elementary school. This type of research is the development of the ADDIE model. The research subjects were six experts consisting of four material experts and two media experts. The test subjects were two teacher practitioners and ten students. The data collection method used is a questionnaire. The instrument used to collect data is a rating scale. Data analysis techniques are descriptive qualitative, and quantitative. The study results are the assessments obtained from material experts, namely 94% (very good). The assessment of learning media experts is 95% (very good). The assessment of the practicality of the media given by the teacher is 94% (very good) and 90% of students (very practical). It was concluded that the QR Code Assisted Pop-up book Media received valid and practical qualifications to be suitable for use in learning.